Model of Stages of Implementation of E-Government Development in Organizational Transformation in the Provision of Integrated Public Services in the Maros Regency MPP - Muhammad Nur; Badu Ahmad; Muh Tang Abdullah (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Organizational transformation in e-government development is key to improving the effectiveness of public service delivery, particularly in the Maros Regency Public Service Mall (MPP) as a model for cross-agency service integration. This study aims to analyze the stages of e-government implementation in the organizational transformation process at the Maros Regency MPP using Layne and Lee's (2001) four-stage framework: catalog, transaction, vertical integration, and horizontal integration. Through a qualitative approach with a descriptive design, this study focuses on how the process and identification of the stages of e-government implementation are formed. The study also examines the dynamics of organizational adaptation, resource readiness, and inhibiting and driving factors that influence the continuation of the transformation towards full integration. Data were collected through in-depth interviews, document analysis, and observations of service workflows at the MPP. The results of the analysis are expected to provide a comprehensive picture of the position of the e-government development stages at the Maros MPP, while also providing theoretical contributions through model findings to the study of public sector organizational transformation in accelerating the integration of digital-based services.